Long‐term outcomes of pulmonary metastasectomy: a multicentre analysis. Issue 6 (18th April 2021) - Yaftian, Nima; Dunne, Benjamin; Antippa, Phillip N.; Cheung, Francis P.; Wright, Gavin M.
Abstract : Many extrapulmonary neoplasms metastasize to lung. Pulmonary metastasectomy is safe and is associated with survival of greater than 50% at 5 years in select patients. Abstract: Background: Many extrapulmonary neoplasms metastasize to the lungs. We conducted a retrospective review of all patients who underwent pulmonary metastasectomy for oligometastatic disease at two centres in order to determine long‐term outcomes. Methods: The study institutions' thoracic surgery databases were searched for all patients who underwent pulmonary metastasectomy from 2000 to 2017. Results: There were a total of 476 patients who underwent pulmonary metastasectomy. Mean age at time of surgery was 57.2 ± 15.9 years. Mean number of pulmonary lesions was 1.9 ± 1.6. Mean disease‐free interval (DFI) was 3.6 ± 4.3 years. The most common primary neoplasms were colorectal cancer (CRC) in 35.1% (167/476), sarcoma in 23.9% (114/476), melanoma in 16.2% (77/478), renal cell carcinoma (RCC) in 7.3% (35/476) and germ cell tumour (GCT) in 4.4% (21/476). Hospital mortality was 0.4% (2/476). Mean follow‐up time was 3.8 ± 2.9 years. Survival was 88.9% (95% confidence interval 85.77–91.5) at 1 year and 49.6% (95% confidence interval 44.4–54.6) at 5 years. On multivariate Cox‐regression analysis GCT ( P  = 0.004), CRC ( P  = 0.03), DFI of 36+ months ( P  = 0.007), R0 resection ( P  = 0.002) and non‐anatomical, sub‐lobar (wedge) resection ( P  = 0.002) were protective against mortality. Conclusion: Pulmonary metastasectomy is associated with survival of 50% at 5‐year follow‐up. DFI of over 36 months, R0 resections, lesions resectable by wedge resection rather than anatomic resection and GCT and CRC primary cancers were associated with improved survival.